PERLINDUNGAN PENGGUNA DAN TRIBUNAL TUNTUTAN PENGGUNA MALAYSIA: SOROTAN LITERATUR: Consumer Protection According to Islam and Its Assurance Through the Tribunal for Consumer Claims Malaysia: A Review of Literatures - Mohd Amin, Nadiatul Husna; Zakaria, Zalina; Daud, Mohd Zaidi (Journal of Shariah Law Research, 2022)
Consumer protection laws exist to prevent dangerous or unethical business practices, such as false advertising or faulty products. Until today, there are various consumer laws that have been enforced by the government to provide the best protection to consumers in Malaysia. This includes the establishment of the Tribunal for Consumer Claims Malaysia (TTPM) under the Consumer Protection Act 1999 which was created as a redressing medium to consumers. Deploying a qualitative approach, this article discusses the conceptual aspects of consumer protections both in Islamic and legal perspectives, by looking at the previous literatures. It then goes further by discussing at the roles played by TTPM followed by certain limitations that have surrounded TTPM.